Congenital Pseudoarthrosis of the Tibia: Case Reports - Bulut, Mehmet; Karakut, Lokman; Belhan, Oktay; Sagiroglu, Muhittin Soner; Gurger, Murat (Derman Medical Publ, 2015)
Congenital pseudoarthrosis of the tibia is rarely seen disease which is very difficult to treat. Congenital pseudoarthrosis of the tibia is frequently seen together with neurofibromatosis. Especially according to Boyd classification, type II and V are in the high risk group. In this study, we presented the treatment result of the three years old male patient with type V congenital pseudoarthrosis of the tibia.
Konjenital tibia psödoartrozu: Olgu sunumu
Keywords: Congenital Pseudoarthrosis; Ilizarov; Intramedullary Fixation